Rationale and design for the Asia BP@Home study on home blood pressure control status in 12 Asian countries and regions - Kario, Kazuomi; Tomitani, Naoko; Buranakitjaroen, Peera; Chen, Chen Huan; Chia, Yook Chin; Divinagracia, Romeo; Park, Sungha; Shin, Jinho; Siddique, Saulat; Sison, Jorge; Soenarta, Arieska Ann; Sogunuru, Guru Prasad; et al. (Wiley, 2017)
Home blood pressure (BP) monitoring is endorsed in multiple guidelines as a valuable adjunct to office BP measurements for the diagnosis and management of hypertension. In many countries throughout Asia, physicians are yet to appreciate the significant contribution of BP variability to cardiovascular events. Furthermore, data from Japanese cohort studies have shown that there is a strong association between morning BP surge and cardiovascular events, suggesting that Asians in general may benefit from more effective control of morning BP. We designed the Asia BP@Home study to investigate the distribution of hypertension subtypes, including white-coat hypertension, masked morning hypertension, and well-controlled and uncontrolled hypertension. The study will also investigate the determinants of home BP control status evaluated by the same validated home BP monitoring device and the same standardized method of home BP measurement among 1600 or more medicated patients with hypertension from 12 countries/regions across Asia.